WHY THE USE OF ORAL EMERGENCY CONTRACEPTION IS DELAYED IN THE PUBLIC SECTOR - Távara Orosco, Luis (2015)
At the risk of turning into an excess treating this issue, since in recent times it has abounded in information and discussions about it, we wanted to write this note, in order to say our word in condition of specialist professional problems women's health.